ANALYSIS OF THE ENGLISH TEACHING WRITING METHODS USED BY THE TEACHERS DURING THE COVID-19 PANDEMIC AT EMSA SCHOOL - Metanoia Tatag Pujianti; Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2022)
The condition of the education system that changed from a face-to-face learning system to an online learning system as a reaction to the spread of the COVID-19 virus throughout Indonesia made this an inspiration for researchers to conduct research. Of course, given the new education system, teachers must develop efficient teaching techniques to optimize student learning. This study intends to describe the methods teachers use to teach English lessons online during the pandemic. The purpose of this study is to analyze the teachers' methods for teaching English during the COVID-19 pandemic: (1) the strategies that teacher used during COVID-19 pandemic to teaching writing, (2) the reasons of selecting those strategies. In order to create this thesis, the researcher used descriptive qualitative methods. Since the researcher completed a one- month internship at a school on October 25, 2022, the study data has been assessed. Two English teachers from EMSA School were interviewed to gather information.The findings of this study are as follows: (1) explain various devices to tech and providing detailed instruction on how to submit the assignment, (2) explain the use of online tools as the effective way, (3) evaluating the student’s comprehension of the materials, reminding students for the schedule and using online tools to provide the assignment. Key words: Teachers’ strategies, online learning, online platform.